2004
DOI: 10.1021/nl0349505
|View full text |Cite
|
Sign up to set email alerts
|

SiO2-Coated CdTe Nanowires:  Bristled Nano Centipedes

Abstract: CdTe nanowires with bristled SiO 2 coatings resembling nanoscale centipedes were produced in a modified Sto 1ber process when mercaptosuccinic acid was used as a stabilizer. The reason for the unusual morphology of the coating is believed to be the nonuniform distribution of the stabilizers on the surface of the nanowire. Atomistic calculations of CdTe nanoparticles as a simplified model of a nanowire surface reveal that phase separation of the mercaptosuccinic acid and (3-mercaptopropyl)trimethoxysilane is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 49 publications
2
88
0
Order By: Relevance
“…It has been reported that Cd 2+ is released from CdSe through oxidative attack. 16,17 This released cadmium can bind to the sulfohydryl groups of critical mitochondria proteins leading to mitochondria dysfunction and ultimately cell poisoning. 18 Qdots are small fluorescent tags that have tremendous potential for advancing knowledge in biology because of their unique characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Cd 2+ is released from CdSe through oxidative attack. 16,17 This released cadmium can bind to the sulfohydryl groups of critical mitochondria proteins leading to mitochondria dysfunction and ultimately cell poisoning. 18 Qdots are small fluorescent tags that have tremendous potential for advancing knowledge in biology because of their unique characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Several surfactants have been used for synthesizing CdTe quantum dots in the aqueous phase, namely, thioglycolic acid (TGA) [48][49][50], mercaptopropionic acid (MPA) [47], mercaptosucinnic acid (MSA) [51][52], glutathione (GSH) [53], and cysteine (Cys) [54]. TGA, MPA, and MSA are short stabilizing agents and they are commonly used to fabricate water-dispersible CdTe QDs in a one-pot synthesis.…”
Section: Preparation Of Cdte Quantum Dots In the Aqueous Phasementioning
confidence: 99%
“…In recent years, nano-structures have attracted much attention due to their potential applications in fabricating nanometer-scale devices possessing a variety of interesting functions [5,6]. Among the methods used to coat the nano-structures to protect against wear and to provide corrosion resistance, a number of researchers have used Si oxide to provide functionality to nano-powders for surface treatment [7,8].…”
Section: Introductionmentioning
confidence: 99%